2009
DOI: 10.2106/jbjs.h.00665
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life During Orthopaedic Training and Academic Practice

Abstract: Despite reporting high levels of job satisfaction, orthopaedic residents and faculty are at risk for burnout and distress. Identification of protective factors and risk factors may provide guidance to improve the quality of life of academic orthopaedic surgeons in training and beyond.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
170
2
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(176 citation statements)
references
References 43 publications
3
170
2
1
Order By: Relevance
“…3 Residents within a relationship and, in particular, male residents with a significant other or a spouse, had a significantly higher prevalence of burnout. This finding is somewhat surprising, as previous studies in the general medical specialties 4,23,24 and in orthopedic surgery residents 24,25 have shown that unmarried residents have higher rates of burnout and that male spouses of orthopedic residents were significantly less satisfied with the quality of their relationships than were spouses of male residents. Moreover, female residents seem to experience more stress-related health complaints than their male colleagues.…”
Section: Discussionmentioning
confidence: 74%
“…3 Residents within a relationship and, in particular, male residents with a significant other or a spouse, had a significantly higher prevalence of burnout. This finding is somewhat surprising, as previous studies in the general medical specialties 4,23,24 and in orthopedic surgery residents 24,25 have shown that unmarried residents have higher rates of burnout and that male spouses of orthopedic residents were significantly less satisfied with the quality of their relationships than were spouses of male residents. Moreover, female residents seem to experience more stress-related health complaints than their male colleagues.…”
Section: Discussionmentioning
confidence: 74%
“…[8][9][10] Clinician burnout is associated with worse patient safety [11][12][13][14][15] and satisfaction. [16][17][18] By some estimates, burnout affects nearly half of all US nurses and physicians.…”
Section: Introductionmentioning
confidence: 99%
“…Employees who experience long work hours, excessive clinical workloads, a chaotic work environment, or discord among fellow staff are more likely to have burnout. 5,8,10,20 Conversely, those who report a greater institutional emphasis on quality of care, team cohesiveness and communication are less likely to report burnout. 5 Adequate staffing levels, equitable distribution of…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When a surgeon suffers emotionally, the collateral damage extends to patients, friends, family, and loved ones [10]. Behavioral problems and dysfunctional thinking, left untreated, tend to worsen over time, and may lead to destructive behaviors that will likely bleed into one's personal and professional life.…”
mentioning
confidence: 99%